Penerapan Manajemen Kas Dalam Kaitannya Dengan Pengendalian Kas, Hutang Dan Piutang Dengan Memanfaatkan Laporan Arus Kas (Studi Kasus Pada PDAM Tirta Pakuan Kota Bogor) - Budiman, Asteria Caterinah; Pamungkas, Bambang (Institut Bisnis dan Informatika Kesatuan, 2014)
Cash is a firm’s most liquid asset and has a decisive position in keeping the smooth operations of the company. The larger the cash, the more liquid the company be. But larger cash means also low cash turnover. Thus, a cash management is necessary to effectively and efficiently manage the firm’s liquid asset. This research is aimed at investigating how PDAM Tirta Pakuan implement its cash management and relate it with the control of cash-in-flow and cash-out-flow by utilizing the firm’s the cash flow. The result shows that PDAM TPKB implements its cash management and cash budget in the beginning of period based on previous year’s report. The predicted budget for cash outflow when compared with its realization in 2009 tend to be unfavorable for the firm, however the deviation is contradictive in 2010.